Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Weak phylogenetic effect on specialist plant assemblages and their persistence on habitat islands - Adam Klimeš; Rafael Molina‐Venegas; Angelino Carta; Milan Chytrý; Luisa Conti; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; Francisco E. Méndez‐Castro; David Zelený; et al. (Journal of Biogeography, 2024)
Aim The influence of species phylogenetic relatedness on the formation of insular assemblages remains understudied in functional island biogeography, especially for terrestrial habitat islands (i.e. distinct habitat patches embedded in a matrix that differ in the prevailing environmental conditions). Here, we tested three eco‐evolutionary hypotheses: (1) functional specialization of species (i.e. specialism) is associated with phylogenetic clustering at the habitat archipelago scale, (2) such clustering increases with insularity at the habitat island scale and (3) traits indicative of effective local persistence strategies shape island specialism. Location Terrestrial habitat islands, Europe (Fens in the Western Carpathians, Outcrops in Moravia and Mountaintops in the Cantabrian Range). Taxon Angiosperms. Methods We assessed the phylogenetic relatedness of habitat specialists in three different archipelagos composed of terrestrial habitat islands based on phylogenetic signals and phylogenetic diversity (PD) measures. We estimated the effect of insularity on PD using linear models and the effect of persistence traits on specialism using phylogenetic logistic regressions. Results Our hypotheses were largely not supported. Outcrop and mountaintop specialist assemblages did not exhibit any phylogenetic structuring, whereas fen specialists were clustered at the archipelago scale. Therefore, insularity seems not to act as a selective force for phylogenetic structure, and ecologically important persistence traits do not operate as precursors of specialism. Main Conclusions Our results show that species phylogenetic relatedness plays a minor role in shaping habitat island specialist assemblages. Furthermore, the effects of phylogenetic relatedness on assemblages of island specialists are system and scale dependent. Finally, accounting for species' phylogenetic relatedness on persistence traits yielded results similar to previous studies, which corroborates the positive relationship between insularity and functional traits (indicative of enhanced plant persistence abilities with increasing within‐archipelago insularity).

From land to glass: An integrated approach for quality and traceability assessment of top Italian wines - Marcelo Enrique Conti; Mattia Rapa; Cristina Simone; Mario Calabrese; Gerardo Bosco; Silvia Canepari; Maria Luisa Astolfi (Food Control, 2024)

Effect of light and feeding regimes on the daily rhythm of thermal preference in Nile tilapia (Oreochromis niloticus) - Gonzalo de Alba; Francesca Conti; Jorge Sánchez; Laura Michelle Godoy; Francisco Javier Sánchez-Vázquez; José Fernando López-Olmeda; Luisa María Vera (Aquaculture, 2024)

The relationship between spectral and plant diversity: Disentangling the influence of metrics and habitat types at the landscape scale - Michela Perrone; Mirko Di Febbraro; Luisa Conti; Jan Divíšek; Milan Chytrý; Petr Keil; Maria Laura Carranza; Duccio Rocchini; Michele Torresani; Vítězslav Moudrý; Petra Šímová; Dominika Prajzlerová; et al. (Remote Sensing of Environment, 2023)

Biomonitoring of element contamination in bees and beehive products in the Rome province (Italy) - Marcelo Enrique Conti; Maria Luisa Astolfi; Maria Grazia Finoia; Lorenzo Massimi; Silvia Canepari (Environmental Science and Pollution Research, 2022)

Insularity promotes plant persistence strategies in edaphic island systems - Luisa Conti; Francisco E. Méndez‐Castro; Milan Chytrý; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; David Zelený; Gianluigi Ottaviani (Global Ecology and Biogeography, 2022)
Aim Trait‐based approaches are being used increasingly in island biogeography, providing key insights into the eco‐evolutionary dynamics of insular systems. However, the determinants of persistence of plant species after they have arrived and established on an island remain largely unexplored. Here, we used three edaphic island systems (i.e., habitat patches distinguished from the landscape matrix by distinct soil conditions and specialized vegetation) to examine relationships between persistence strategies (those associated with clonality, bud bank, seed mass and life‐form) and insularity. We hypothesized that insularity promotes and selects strategies to persist locally, such that species occurring on small and/or isolated edaphic islands show trait values indicative of enhanced persistence and lower functional diversity. Location Three European systems of edaphic islands in the Western Carpathians, Moravia and the Cantabrian Range. Time period Present. Major taxa studied Vascular plants. Methods For each system, we used linear models to explore persistence‐related plant trait patterns (mean trait values and functional diversity) in relationship to three insularity metrics (island size, isolation and target effect). We focused on patterns of edaphic island specialists because their presence is confined to the islands. Results We found that insularity metrics largely explained the variation of the mean value and diversity of persistence‐related traits of edaphic island plant specialists. Specifically, insularity was positively related to traits supporting local persistence (e.g., more extensive lateral spread) and to a reduced variability in persistence traits. More insular systems showed stronger and more numerous trait–insularity links. Main conclusions Insularity can affect plant species diversity, form and function in edaphic island systems, such as selecting for enhanced and less diverse persistence strategies. Plant species occurring in insular systems might therefore avoid or delay local extinction by promoting adaptive strategies to persist in situ .

Microfabricated cantilevers for parallelized cell-cell adhesion measurements - Michele Zanetti; Suet Nee Chen; Martina Conti; Matthew R. G. Taylor; Orfeo Sbaizero; Luisa Mestroni; Marco Lazzarino (European Biophysics Journal, 2022)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Community assembly processes along a sub-Mediterranean elevation gradient: analyzing the interdependence of trait community weighted mean and functional diversity - Alessandro Bricca; Luisa Conti; Maria Federico Tardella; Andrea Catorci; Marco Iocchi; Jean-Paul Theurillat; Maurizio Cutini (Plant Ecology, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Simulating plant invasion dynamics in mountain ecosystems under global change scenarios - Marta Carboni; Maya Guéguen; Ceres Barros; Damien Georges; Isabelle Boulangeat; Rolland Douzet; Stefan Dullinger; Guenther Klonner; Mark van Kleunen; Franz Essl; Oliver Bossdorf; Emily Haeuser; et al. (Global Change Biology, 2018)
Across the globe, invasive alien species cause severe environmental changes, altering species composition and ecosystem functions. So far, mountain areas have mostly been spared from large‐scale invasions. However, climate change, land‐use abandonment, the development of tourism and the increasing ornamental trade will weaken the barriers to invasions in these systems. Understanding how alien species will react and how native communities will influence their success is thus of prime importance in a management perspective. Here, we used a spatially and temporally explicit simulation model to forecast invasion risks in a protected mountain area in the French Alps under future conditions. We combined scenarios of climate change, land‐use abandonment and tourism‐linked increases in propagule pressure to test if the spread of alien species in the region will increase in the future. We modelled already naturalized alien species and new ornamental plants, accounting for interactions among global change components, and also competition with the native vegetation. Our results show that propagule pressure and climate change will interact to increase overall species richness of both naturalized aliens and new ornamentals, as well as their upper elevational limits and regional range‐sizes. Under climate change, woody aliens are predicted to more than double in range‐size and herbaceous species to occupy up to 20% of the park area. In contrast, land‐use abandonment will open new invasion opportunities for woody aliens, but decrease invasion probability for naturalized and ornamental alien herbs as a consequence of colonization by native trees. This emphasizes the importance of interactions with the native vegetation either for facilitating or potentially for curbing invasions. Overall, our work highlights an additional and previously underestimated threat for the fragile mountain flora of the Alps already facing climate changes, land‐use transformations and overexploitation by tourism.

Multifaceted Analysis of Patch-Level Plant Diversity in Response to Landscape Spatial Pattern and History on Mediterranean Dunes - Marco Malavasi; Luisa Conti; Marta Carboni; Maurizio Cutini; Alicia T. R. Acosta (Ecosystems, 2016)

Merkel cell carcinoma: a population-based study on mortality and the association with other cancers - Valeria Ascoli; Giada Minelli; Mark Kanieff; Luisa Frova; Susanna Conti (Cancer Causes & Control, 2011)

Volatile chemical composition and bioactivity of six essential oils against the stored food insect Sitophilus zeamais Motsch. (Coleoptera Dryophthoridae) - Alessandra Bertoli; Barbara Conti; Valerio Mazzoni; Laura Meini; Luisa Pistelli (Natural Product Research, 2011)

Infra-red laser irradiation enhances interleukin-1 receptor antagonist, increases 3H-thymidine incorporation and the release of [3H]arachidonic acid in human monocytes - Marcella Reale; Claudio Orso; Maria Luisa Castellani; Renato Carmine Barbacane; Fernanda Cristina Placido; Ettore Porreca; Concetta Di Febbo; Ivana Cataldo; Demetrio Vacalis; G. Anogianakis; A. Trakatellis; Pio Conti (Molecular and Cellular Biochemistry, 1997)